Peranan Ojk Dalam Penanganan Investasi Bodong/Ilegal/Fiktif - Fadhilah Agustina; Khadziq Khadziq; Rynanda Rizqy Amrulloh (Universitas Kristen Indonesia Toraja, 2023)
The fastest growing financial sector is investment activity. The investment business is certainly included in the scope of supervision by the Financial Services Authority. But in practice, many people carry out their rotten ideas for personal gain which can harm many parties who invest in these people or individuals. The rise of fraudulent investments is certainly part of the responsibility and supervision carried out by the Financial Services Authority. This research is qualitative research using the literature study approach method, the data collection refers to previous research, books, newspapers, documents, and other reading sources. This research focuses on discussing the role of the OJK in preventing and eradicating illegal/bodong/fictitious investments. In an effort to regulate and prevent fraudulent investment practices, the actions launched by OJK are conducting socialization and counseling to the public, providing investment entity establishment licenses only to those who meet the criteria, providing consumer complaint services, forming a fraudulent investment alert task force, issuing regulations and forming capital market protection institutions. The obstacles in efforts to eradicate fraudulent investment are in the form of difficulties in establishing communication between institutions, there is a barrier between OJK and Bank Indonesia as the highest supervision of the financial and banking sectors in Indonesia, this is due to the distance and long transition from OJK to Bank Indonesia.